On-line identification of squeeze-film dynamics of multi-mode rotor-bearing system - Yu, Zhou; Meng, Lim Tau (Computer Assisted Methods in Engineering and Science, 2023)
This paper presents a practical algorithm for on-line parameter identification of squeeze-film bearing of multi-mode rotor-bearing system. The identification procedure is based on modeling each of the bearing pedestal by applying a multi-frequency excitation force on the rotor and frequency transfer function data are used. It suggested that accurate identification coefficients with reduced standard errors can be achieved without resource to full or reduced-order rotor system measurements. The approach can be applied to rotor-bearing system with any degree of complexity and other types of bearing. Simulation and experimental investigation show that the identification algorithm developed in the paper will considerably simplify the measurement and calculation task for testing work in laboratory and industrial environment without any lost of identification accuracy. The experimental results of stiffness and damping characteristics of the 'squeeze-film bearings for different rotating speed are also presented.